Electrical conductivity and optical properties of copolymers based on 4-vinylpyridine and tetralincyclobutylhydroxyethylmethacrylate - Aydogdu, Y; Erol, I; Yakuphanoğlu, Fahrettin; Aydogdu, A; Ahmedzade, M (Elsevier Science Sa, 2003)
The electrical conductivity and the optical absorption of the 4-vinylpyridine and amorphous tetralincyclobuty lhydroxyethylmethacrylate poly (TCHEMA-co-4VP) copolymers, which were prepared with three different compositions by using polymerization technique, were studied and the obtained results were analyzed. The conduction mechanisms of samples were determined via DC and AC electrical conductivity measurements. The DC plots of samples suggested that there were two types of conduction channels contributing to conductivity. Their electrical conductivities were found in range 10(-9) to 10(-8) S/cm at room temperature. Also, the dependence of AC conductivity to frequency was detected as omega(0.91-0.96). The optical band gaps of samples were determined by means of optical absorption spectra and found as 1.79, 3.27 and 3.14 eV for PVP60, PVP70 and PVP80, respectively. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: copolymer; electrical conductivity; optical